2021
DOI: 10.1111/ajag.13007
|View full text |Cite
|
Sign up to set email alerts
|

Lifespace metrics of older adults with mild cognitive impairment and dementia recorded via geolocation data

Abstract: Objective: Lifespace, the physical area in which someone conducts life activities, indicates lived community mobility. This study explored the feasibility of technology-based lifespace measurement for older people with dementia and mild cognitive impairment (MCI), including the generation of a range of lifespace metrics, and investigation of relationships with health and mobility status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…GPS technologies are emerging as a solution to monitor mobility and life space patterns in PwD. Across nine of the included studies [22,37,38,40,42,45,[48][49][50], GPS-derived mobility outcomes broadly agreed with travel diaries completed by participants. This is congruent with work in healthy older adults and populations with non-dementia neurodegenerative disorders [19][20][21].…”
Section: Overall Findingsmentioning
confidence: 89%
See 1 more Smart Citation
“…GPS technologies are emerging as a solution to monitor mobility and life space patterns in PwD. Across nine of the included studies [22,37,38,40,42,45,[48][49][50], GPS-derived mobility outcomes broadly agreed with travel diaries completed by participants. This is congruent with work in healthy older adults and populations with non-dementia neurodegenerative disorders [19][20][21].…”
Section: Overall Findingsmentioning
confidence: 89%
“…Kaspar et al defined a valid day as having <1 h of missing data whereas Oswald et al considered a day valid if there were no invalid hours, with an invalid hour having <30 min of valid GPS data [37,38]. The home radius, the set radius around the home coordinates used to determine if the participant left their home, varied across studies with values ranging from approximately 25 m [28] to 500 m [49]. Studies commonly agreed that a visited location is a GPS data point which has the same coordinates for at least 5 min.…”
Section: Gps Data Processingmentioning
confidence: 99%
“…Other research by an investigator (JL) has successful recorded outdoor locations using GPS on a smartphone, a passive data collection method with older people with mild cognitive impairment and dementia (31). This approach resulted in participants recording a mean of 161.5/168 h in a week of recording.…”
Section: Discussionmentioning
confidence: 99%
“…Other research investigating community participation uses the construct of lifespace, the geographic area where an individual lives and carries out their life. Lifespace measurement has been used mostly in relation to older people including those with mild cognitive impairment and dementia (31) and is measured more recently through the passive collection of the recording of outdoor locations using GPS on a smartphone. The data are then converted to metrics including areas, percentage of time at home and number of times leaving the home.…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen studies were identified in this category, and all applied GPS as a space-based technology to gather tracking data in exploring patients' behavior patterns. In most studies, analysis and interpretation of spatial GPS data were used to assess patients' out-of-home behavior [20][21][22][23], mobility patterns [52,53,65,[114][115][116][117], life-space metrics [118,119], and driving behavior [24,25]. In one study, GPS data were used to propose a Bayesian classifier model to estimate the probability of wandering [120].…”
Section: Basic Researchmentioning
confidence: 99%